House rental advertisement for UiTM Jasin student using the filtering technique / Asyraff Aizzat Zaidi and Norbahiyah Awang - Zaidi, Asyraff Aizzat; Awang, Norbahiyah (Faculty of Computer and Mathematical Sciences, 2021)
Student affordance on choosing the right house rental for them during their study had been less concerned due to not many factors effecting the choice of choosing the house. Some students prefer to live in a campus while some of them prefer to live outside of the campus. Jasin is one district in Melaka that have high population of students. Searching for the house rental might be a problem for them due to awareness about the available of the house rental from the home owner. During the whole study of this project, some problem arises for the students regarding the search for the house rental. Some students want to rent house based on their preferences, and some of them did not have any specific criteria for house rental. These factors could lead to implementing one solution for them in order to ease them on searching for the house rental. Developing of the system required many works such as information gathering, requirement analysis and developing design. All this process is crucial in order for the system to be developed. The House Rental Advertisement for UiTM JASIN Students Using Filtering Technique was being developed in order to give them a solution regarding the problem that arise.